Proceedings of the 16th International Symposium on Management (INSYMA 2019) 2019
DOI: 10.2991/insyma-19.2019.8
|View full text |Cite
|
Sign up to set email alerts
|

Company performance before and after a merger

Abstract: This study aims to compare the financial performance of non-finance companies listed on the Indonesia Stock Exchange for the period 2010-2014 before and after a merger and acquisition. This study used the long-term pre and post-merger financial data to investigate the long-term performance. The present work conducted a comprehensive ratio analysis of 14 major ratios related to profitability, efficiency, leverage, and liquidity. The method used in testing the research was a quantitative approach with paired t-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
5
5
0
Order By: Relevance
“…The post-merger shareholder earnings also improve in the post-merger because most government policies favour the food and agriculture industries because of their significant contribution to economic growth; for example, in terms of GDP. The results are in line with studies of other Indian industries both in case of domestic and international [8,18,20,28,39,[51][52][53][54][55]. It can be inferred that M&A produces results in the long term.…”
Section: Discussionsupporting
confidence: 88%
“…The post-merger shareholder earnings also improve in the post-merger because most government policies favour the food and agriculture industries because of their significant contribution to economic growth; for example, in terms of GDP. The results are in line with studies of other Indian industries both in case of domestic and international [8,18,20,28,39,[51][52][53][54][55]. It can be inferred that M&A produces results in the long term.…”
Section: Discussionsupporting
confidence: 88%
“…Their findings showed that the operating performance, financial performance and shareholders' wealth increased during the post-M&A period but were statistically insignificant. Beverly et al (2019) analysed the financial performance of Indonesian non-financial companies, from 2010 to 2014, using 14 major ratios related to profitability, leverage, efficiency and liquidity. They found that merging firms had outperformed during the post-merger period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After the results appeared from different tests, the next step was to draw conclusions. The basis for drawing conclusions from these statistical results is if the probability is less than α, then the research hypothesis was not rejected, Beverly [12]. This means there is a significant difference between bank performance, credit, market, liquidity, operational, and bank capital level before and after the merger.…”
Section: The Results Of Analysis Of Bank Performance Tests Before And...mentioning
confidence: 98%